Validated Intervention Mapping Module for Menstrual Hygiene Skills: Modul Intervention Mapping Tervalidasi untuk Keterampilan Menstrual Hygiene - Indriyani, Lujeng; Sukinah, Sukinah (Pedagogia : Jurnal Pendidikan, 2026)
General Background: Menstrual hygiene education is essential for students with mild intellectual disabilities because they often experience difficulties in understanding puberty and practicing self-care independently. Specific Background: Pre-menstrual learning in special education remains limited, incidental, and lacks structured visual teaching materials. Knowledge Gap: Existing studies have rarely developed comprehensive modules that combine conceptual understanding, practical skills, teacher guidance, and integrated evaluation. Aims: This study developed an Intervention Mapping-based pre-menstrual learning module to improve students’ menstrual hygiene understanding and skills. Results: Needs analysis showed that students required concrete, visual, gradual, and skill-oriented materials, while teachers needed systematic guidance. The developed student module and teacher guide were rated Good to Excellent by experts. Initial trials showed positive responses, and paired sample t-test results indicated significant gains in understanding and skills. Novelty: The study applies Intervention Mapping to adaptive reproductive health teaching materials. Implications: The module supports structured, accessible, and behavior-oriented menstrual hygiene learning in special education. Highlights• Students required concrete, visual, gradual, and skill-oriented learning materials.• Expert validation placed the student module and teacher guide in feasible categories.• Post-test results showed significant gains in understanding and practical hygiene skills. KeywordsIntervention Mapping; Menstrual Hygiene; Mild Intellectual Disability; Learning Module; Special Education